1998
DOI: 10.1086/514599
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Infection Is a Risk Factor for Invasive Aspergillosis in Lung Transplant Recipients

Abstract: Invasive aspergillosis (IA) remains a major cause of morbidity and mortality following solid organ transplantation. To assess the incidence of IA following lung transplantation and to identify risk factors for its occurrence, we performed a case-control study involving 101 patients undergoing lung transplantation at our institution from 1990 to 1995 and reviewed the findings. Fourteen patients (14%) developed IA. The mean time from transplantation to diagnosis was 15 months. Nine patients died; the mean time t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
103
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(108 citation statements)
references
References 7 publications
3
103
1
1
Order By: Relevance
“…[27][28][29] In our series, Aspergillus infection was not related with neutropenia or acute GVHD, probably because 41% of cases were autologous transplants and the number of patients with long-standing neutropenia or severe acute GVHD was low. An association between CMV disease and fungal infections has been noted not only in solid organ transplant recipients 30,31 but also in recipients of HSCT. [32][33][34] The relationship between both pathogens remains obscure.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] In our series, Aspergillus infection was not related with neutropenia or acute GVHD, probably because 41% of cases were autologous transplants and the number of patients with long-standing neutropenia or severe acute GVHD was low. An association between CMV disease and fungal infections has been noted not only in solid organ transplant recipients 30,31 but also in recipients of HSCT. [32][33][34] The relationship between both pathogens remains obscure.…”
Section: Discussionmentioning
confidence: 99%
“…[45][46][47][48] Nichols et al 49 showed an increased risk particularly for patients during primary infection (D þ /R À ). In our study, HCMV viremia, also without subsequent HCMV disease, seems to be a risk factor for the development of non-viral opportunistic infections.…”
Section: Discussionmentioning
confidence: 99%
“…15 Recipient CMV seropositivity is a significant risk factor in bone marrow transplant patients. 7 However, posttransplant CMV infection has not been clearly shown to increase risk for IA.…”
Section: Discussionmentioning
confidence: 99%